Research on construction of indicator system for evaluation of the ecological civilization education in Chinese universities. (December 2018) - Ren, Ping; Liu, Xi; Liu, Jingwei
Abstract: Ecological civilization education is a critical, educational support for construction of ecological civilization. The structure chart of ecological education evaluation below shows that process evaluation plays a decisive role in determining the results of summary evaluation. The construction of an indicator system in this paper is just by focusing on the core content of ecological education –Educational PROCESS – so to incorporate the theory of ecological civilization into the whole college education. This paper is based on the modified AHP (Analytic Hierarchy Process) to establish a comprehensive evaluation model, construct judgment matrix and correct the weights, and to construct the framework and indicator system for evaluation of ecological civilization education in colleges and universities.